ej-sa-2017 at SemEval-2017 Task 4: Experiments for Target oriented Sentiment Analysis in Twitter - Dovdon, Enkhzol (2017)
This paper describes the system we have used for participating in Subtasks A (Message Polarity Classification) and B (Topic Based Message Polarity Classification according to a two-point scale) of SemEval2017 Task 4 Sentiment Analysis in Twitter. We used several features with a sentiment lexicon and NLP techniques, Maximum Entropy as a classifier for our system.